Mind over matter, matter over mind a discourse deviation approach to F. Sionil Jose's Ermita - Suguitan, Cynthia Grace B. (2007)
My study is an attempt to look into the value of Guy Cook's theory of discourse deviation as a tool in analyzing Philippine literature in English. It will consider how the framework of discourse deviation may enrich the reading of Philippine literature. Cook's model, which is explained in his book Discourse and Literature: the Interplay of Form and Mind (1994), draws on important concepts from schema theory, discourse analysis, Artificial Intelligence (AI) text theory, and literary theory, and uses these insights in coming up with a framework that explains how literature can interact with and change a reader's "mental representations of the world" (p. 10) or knowledge about the world. These mental representations (also called schemata) play a role in the processing of a text, but Cook argues that literary texts can also "rebound upon" schemata by refreshing and altering them (p. 10). This refreshing and altering of mental representations by breaking them down, reorganizing them, or building new ones is in fact, according to Cook, one of the functions of literature (p. 10). He further explaions that the literariness of a work lies in discourse deviation -- the dynamic interaction between the linguistic and text structural features of the work on the one hand, and a particular reader's schemata on the other, an interaction whose overall result is to bring about a change in that reader's schemata (p. 182). Because different readers have different interpreting schemata, this leads to different interactions between language and text structure on the one hand, and mental representations on the other hand (p. 182). For this reason, discourse deviation theory (DD) does not assign literariness conclusively to a given text, but only to a certain text in interaction with a particular reader (p. 182). Although Cook's framework assumes the analysis of a text as valid for only one reader, it is likely that the analysis of a text as valid for only one reader, it is likely that the analysis will also "hold true for other readers whose experience of language and the world is sufficiently similar" (pp. 213-214). Using Cook's DD framework in analyzing F. Sionil Jose's Ermita, I will illustrate how the mind affects the processing of "matter" (i.e., something printed or set down in writing -- in this case, the linguistic and text, structural form of the work) via the different interpreting schemata evoked by my reading of the novel. I will also show how matter can affect my mind by refreshing and altering my mental representations of the world. This study hopes to provide an alternative way of reading Philippine literature, an alternative way that can enhance and deepen the Filipino reader's experience of a text.